RELASI ANTARA DESAIN MODEL PEMBELAJARAN, PENDEKATAN STRATEGIS, DAN METODE KOLABORATIF DALAM KONTEKS PENDIDIKAN MODERN - Rohmatun Fitriana (As-Sulthan Journal of Education, 2026)
This study aims to understand the triadic relationship between instructional design models, strategic approaches, and collaborative methods within the modern educational ecosystem. The background of this research is the gap between the theoretical demands of 21st-century learning and the empirical realities in the classroom, where teachers tend to apply these three components separately or inconsistently. The research method used is library research with a qualitative approach through literature studies from various written sources. Data were analyzed using data reduction, data display, and data verification with content analysis, discourse analysis, and interpretive analysis techniques. The findings indicate that the instructional design model functions as a systematic planning framework, the strategic approach serves as an integrative e adhesive and an adaptation instrument to the classroom context, while collaborative methods emphasize active cooperation through various models such as Jigsaw, STAD, and Group Investigation. The relationship among the three is reciprocal determinism (mutually determining) rather than linear. This study concludes that the success of modern learning does not lie in the dominance of any single component, but rather in the creation of a harmonious, adaptive, and mutually reinforcing triadic relationship within diverse classroom contexts.